2010
DOI: 10.1073/pnas.0913209107
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic and systematic aspects of spatial representations in the macaque parietal cortex

Abstract: The sensorimotor transformations for visually guided reaching were originally thought to take place in a series of discrete transitions from one systematic frame of reference to the next with neurons coding location relative to the fixation position (gaze-centered) in occipital and posterior parietal areas, relative to the shoulder in dorsal premotor cortex, and in muscle-or jointbased coordinates in motor output neurons. Recent empirical and theoretical work has suggested that spatial encodings that use a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
123
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(141 citation statements)
references
References 46 publications
13
123
5
Order By: Relevance
“…Instead we found that hand position is in fact coded relative to gaze location at this point in the task, possibly reflecting the immediate behavioral goal of maintaining hand and gaze fixation. The source of this signal could be the PRR or PMd, both of which have similar HϪG encoding during the fixation period (Chang et al, 2009;Pesaran et al, 2010, their supplemental material). The HϪG signal is not maintained throughout the task, but becomes progressively weaker in the population once the reach target is present and the behavioral goal is shifted toward planning the upcoming reach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead we found that hand position is in fact coded relative to gaze location at this point in the task, possibly reflecting the immediate behavioral goal of maintaining hand and gaze fixation. The source of this signal could be the PRR or PMd, both of which have similar HϪG encoding during the fixation period (Chang et al, 2009;Pesaran et al, 2010, their supplemental material). The HϪG signal is not maintained throughout the task, but becomes progressively weaker in the population once the reach target is present and the behavioral goal is shifted toward planning the upcoming reach.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to neighboring PRR where cells usually show a clear cue-related peak, followed by sustained firing during the delay period (see Cui and Andersen, 2011, Figure 3, for examples of population responses for PRR and area 5d). PRR has been found to code reach targets in a predominantly gaze-centered reference frame Batista et al, 1999;Buneo et al, 2002;Cohen and Andersen, 2002;Pesaran et al, 2006, but see Mullette-Gillman et al, 2005Chang and Snyder, 2010;McGuire and Sabes, 2011). There is no a priori reason why cells that code an upcoming reach movement relative to the direction of gaze should also have visually evoked responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This calculation must be based on an estimate of the body's current posture and requires an alignment of the reference frames involved in visual processing and limb movement planning. Whereas saccade planning is thought to occur in eye-centered coordinates, both eye-and body-related reference frames are probably used for limb movement planning (Pesaran et al, 2006;Chang and Snyder, 2007;Marzocchi et al, 2008;Chang et al, 2009;Ferraina et al, 2009;McGuire and Sabes, 2009;Bernier and Grafton, 2010;Chang and Snyder, 2010;Pesaran et al, 2010). The PPC, and especially the SPL, has been suggested to play a major role in the estimation of the current limb positions using proprioceptive and visual information (Graziano et al, 2000;Shadmehr and Krakauer, 2008;Jackson et al, 2009), implicated, for example, by patients suffering from optic ataxia (Karnath and Perenin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Sensory systems are known to process information in frames of reference anchored to specific body-parts (e.g., Graziano, Yap, & Gross, 1994), as well as hybrid frames involving combinations of these (e.g., Carrozzo & Lacquaniti, 1994), and idiosyncratic frames for transformation between body-part anchored frames (e.g., Chang & Snyder, 2010;Gazzaniga, Ledoux, & Wilson, 1977). Though frames of reference of this kind are often called 'egocentric', some are keen to distinguish this range of body-part anchored coding from the 'egocentric' structure of perceptual experience (Brewer & Pears, 1993;Foley et al, 2015;Levinson, 1996).…”
Section: Introductionmentioning
confidence: 99%